Distribution, scale, and drivers of mass mortality events in Europe's freshwater bivalves - Daniel A. Cossey; Maria Urbańska; Ronaldo Sousa; Juergen Geist; Anna Maria Labecka; Şebnem Atasaral; Maciej Bonk; Liliya Bylyna; Frank P. L. Collas; Daniel Daill; Andreas H. Dobler; Noé Ferreira‐Rodríguez; et al. (Conservation Biology, 2026)
Mass mortality events (MMEs) are decimating populations and compromising key ecosystem functions around the globe. One taxon particularly vulnerable to MMEs is freshwater bivalve mollusks. This group has important ecosystem engineering capacities and includes highly threatened and highly invasive taxa. Thus, MMEs of freshwater bivalves have important implications for conservation and ecosystems. Despite this, little is known about the magnitude, frequency, duration, distribution, and causes of freshwater bivalve MMEs. Using a questionnaire, we compiled data from 239 reports describing freshwater bivalve MMEs across 22 European countries since 1960. With these data, we analyzed trends in MME timing, location, and magnitude; identified the species affected; and evaluated the suggested causes (including reporter certainty). We found that the frequency of reports of MMEs increased each year, MMEs affected a broad range of species, clear geographical patterns linking certain causes to specific locations were lacking, factors related to drying and habitat destruction predominated suggested causes, and considerable uncertainty surrounded the causes of many MMEs, particularly those associated with potential pollutants and disease agents. Based on our findings, we recommend the standardization of many aspects of MME research (e.g., reporting and recovery assessment protocols), increased surveying for MMEs, further investigation into the causes of MMEs, especially those with significant uncertainty, and immediate actions to improve waterbody management, mitigate the effects of high temperatures, and further protect freshwater bivalves through the development and implementation of appropriate management actions and legislation.

Halogen enrichment in the North American lithospheric mantle from the dehydration of the Farallon plate - George Segee-Wright; Jaime D. Barnes; John C. Lassiter; Duncan J. Holmes; Grace M. Beaudoin; Rudra Chatterjee; Daniel F. Stockli; J. Elis Hoffmann; Timm John (Geochimica et Cosmochimica Acta, 2023)

Investing in nature-based solutions: Cost profiles of collective-action watershed investment programs - Shiteng Kang; Timm Kroeger; Daniel Shemie; Marta Echavarria; Tamara Montalvo; Leah L. Bremer; Genevieve Bennett; Samuel Roiphe Barreto; Henrique Bracale; Claudia Calero; Aldo Cardenas; Julián Cardona; et al. (Ecosystem Services, 2023)

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

Corrigendum: BIIGLE 2.0 - Browsing and Annotating Large Marine Image Collections - Daniel Langenkämper; Martin Zurowietz; Timm Schoening; Tim W. Nattkemper (Frontiers in Marine Science, 2020)

Ecology of a polymetallic nodule occurrence gradient: Implications for deep‐sea mining - Erik Simon‐Lledó; Brian J. Bett; Veerle A. I. Huvenne; Timm Schoening; Noelie M. A. Benoist; Daniel O. B. Jones (Limnology and Oceanography, 2019)
Abyssal polymetallic nodule fields constitute an unusual deep‐sea habitat. The mix of soft sediment and the hard substratum provided by nodules increases the complexity of these environments. Hard substrata typically support a very distinct fauna to that of seabed sediments, and its presence can play a major role in the structuring of benthic assemblages. We assessed the influence of seafloor nodule cover on the megabenthos of a marine conservation area (area of particular environmental interest 6) in the Clarion Clipperton Zone (3950–4250 m water depth) using extensive photographic surveys from an autonomous underwater vehicle. Variations in nodule cover (1–20%) appeared to exert statistically significant differences in faunal standing stocks, some biological diversity attributes, faunal composition, functional group composition, and the distribution of individual species. The standing stock of both the metazoan fauna and the giant protists (xenophyophores) doubled with a very modest initial increase in nodule cover (from 1% to 3%). Perhaps contrary to expectation, we detected little if any substantive variation in biological diversity along the nodule cover gradient. Faunal composition varied continuously along the nodule cover gradient. We discuss these results in the context of potential seabed‐mining operations and the associated sustainable management and conservation plans. We note in particular that successful conservation actions will likely require the preservation of areas comprising the full range of nodule cover and not just the low cover areas that are least attractive to mining.

BIIGLE 2.0 - Browsing and Annotating Large Marine Image Collections - Daniel Langenkämper; Martin Zurowietz; Timm Schoening; Tim W. Nattkemper (Frontiers in Marine Science, 2017)

Application of Adaptive Starling-Like Controller to Total Artificial Heart Using Dual Rotary Blood Pumps - Boon C. Ng; Peter A. Smith; Frank Nestler; Daniel Timms; William E. Cohn; Einly Lim (Annals of Biomedical Engineering, 2017)

In Vitro Comparison of Active and Passive Physiological Control Systems for Biventricular Assist Devices - Jo P. Pauls; Michael C. Stevens; Emma Schummy; Geoff Tansley; John F. Fraser; Daniel Timms; Shaun D. Gregory (Annals of Biomedical Engineering, 2016)

Biventricular Assist Devices: A Technical Review - Shaun D. Gregory; Daniel Timms; Nicholas Gaddum; David G. Mason; John F. Fraser (Annals of Biomedical Engineering, 2011)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)